Psychosocial Determinants of Living Kidney Donors: A Cross-Sectional Study - Alumran A; Aljanoubi EH; Bureqa AS; Alturki R; Alrayes SA; Alakrawi Z; Alshakhs F; Aljuwair M (Risk Management and Healthcare Policy)
Arwa Alumran,1 Eman Hussain Aljanoubi,1 Amal Salman Bureqa,1 Reem Alturki,2 Saja A Alrayes,1 Zahra Alakrawi,1 Fatima Alshakhs,1 Mona Aljuwair1 1Health Information Management and Technology Department, College of Public Health, Imam Abdulrahman Bin Faisal University, Dammam, 34221, Saudi Arabia; 2Clinical Excellence, Eastern Health Cluster, Ministry of Health, Riyadh, 11176, Saudi ArabiaCorrespondence: Arwa Alumran, Email aalumran@iau.edu.saBackground: End-stage renal disease (ESRD) is a global health issue that significantly impacts patient mortality and morbidity. Living kidney donors play a crucial role in addressing the shortage of available organs for transplantation.Objective: This study aims to identify the characteristics of potential kidney donors at King Fahad Specialist Hospital in Dammam (KFSH-D), Saudi Arabia and to assess the psychosocial factors influencing their willingness to proceed with the donation process.Methods: This cross-sectional study included 1523 individuals who applied to donate kidneys at KFSH-D. Data were retrieved from the hospital’s transplant department electronic database, encompassing psychosocial variables such as gender, marital status, and age, along with the outcomes of donation intentions (ie, proceeded with donation, did not proceed due to unwillingness). Descriptive data analysis was conducted using chi-square tests and independent sample t-tests.Results: Of the 1523 potential donors, 997 proceeded with the donation. Key factors influencing the willingness to donate included gender (χ 2=5.098, P=0.024), age (t=2.175, P=0.030), and existing relationships with recipients (χ 2=162.664, P=0.001). However, marital status, nationality, blood group, BMI, weight, and height were not significantly associated with the decision to donate.Conclusion: Several psychosocial factors significantly influence the willingness of potential donors to complete the donation process. Understanding these factors can enhance predictive models and improve donor recruitment strategies, ultimately increasing the availability of kidneys for transplantation.Keywords: end-stage renal disease, living kidney donation, donor characteristics, psychosocial factors, donor willingness, kidney transplantation, healthcare policy, risk management, predictive models